Visualisasi Konservasi Alam Taman Nasional Ujung Kulon melalui Karya Body Painting - Asyifa Dwi Nihaya; Adhi Kusumastuti (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to develop body painting works inspired by the nature conservation of Ujung Kulon National Park and to determine the feasibility of the resulting works. This study used a Research and Development (R&D) method with the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The works were assessed by three expert validators in the field of make-up: an artistic make-up expert, a beauty lecturer, and a make-up expert. Data were obtained through observation sheets and analyzed using quantitative descriptive techniques with a percentage formula. The body painting works achieved an average score of 87.87%, categorized as very good. These results indicate that the resulting body painting works are worthy of being considered fantasy make-up works that highlight the nature conservation theme of Ujung Kulon National Park. This study not only produced fantasy make-up works but also demonstrated that body painting can be used as an alternative visual medium to convey the message of nature conservation.